COMPARISON OF SHORT-TERM MATERNAL AND NEONATAL OUTCOMES BETWEEN ELECTIVE AND EMERGENT CESAREAN SECTION - SINGLE CENTER EXPERIENCE - Lukic, Relja; Lazić Mitrović, Tanja; Rovčanin, Marija; Tomić, Ana; Zamurović, Milena (Medical Research, 2024)
Introduction/Aim: Increased rates of Cesarean section (CS) and subsequent short-term and long-term maternal complications (MC) and neonatal complications (NC) were reported. The aim of this study was to compare short-term MC and NC between elective and emergent CS.Material and Methods: Data from medical records of pregnant women underwent CS at Gynecology/Obstetrics Clinic „Narodni front“, were retrospectively collected. Inclusion criteria were: low-risk, term monofetal pregnancy with obstetrical CS-indications and other non-life-threatening maternal conditions (ophthalmological, orthopedic, psychiatric, lower genital-tract infections). Short-term MC were: surgical complications, inflammatory syndrome, blood transfusion need, and hospital stay ≥5 days. NC were: respiratory morbidity, asphyxia, sepsis, injuries/lacerations, admission to neonatal intensive-care-unit, hospital stay >4 days.Results: We included 1056 singleton pregnancies. Mean age was 32.63±5.38 years, mainly primipara 566 (53.6%). Out of all CS, 774 (73%) were performed emergently. Cephalopelvic disproportion/fetal macrosomia and other CS indications carried significantly high risk for emergent CS (OR=3.943, 95%CI 2.036-6.5.591; OR=7.560, 95%CI 3.994-8.327, respectively). Regardless of the urgency of CS there were no significant differences in the frequency of MC. Neonatal sepsis was significantely higher after emergent CS (p=0.027), having two-times higher risk for its development (OR=2.070, 95% CI 1.072-3.997). There were no fatal maternal/neonatal outcomes and no need for additional care.Conclusion: There were no notable disparities in MC and NC among individuals who underwent emergent and elective CS. Neonates born through emergent CS had higher risk of developing neonatal sepsis. Indications for CS had a greater impact on short-term mother and fetal outcomes than the type of CS.
Keywords: elective Cesarean section; emergent Cesarean section; early maternal complications; early neonatal complications